The Functions of Non-coding RNAs in rRNA Regulation - Yan, Qi; Zhu, Chengming; Guang, Shouhong; Feng, Xuezhu (Frontiers in Genetics, 2019)
Ribosomes are ribonucleoprotein machines that decode the genetic information embedded in mRNAs into polypeptides. Ribosome biogenesis is tightly coordinated and controlled from the transcription of pre-rRNAs to the assembly of ribosomes. Defects or disorders in rRNA production result in a number of human ribosomopathy diseases. During the processes of rRNA synthesis, noncoding RNAs, especially snoRNAs, play important roles in pre-rRNA transcription, processing, and maturation. Recent research has started to reveal that other long and short noncoding RNAs, including risiRNA, LoNA, and SLERT (among others), are also involved in pre-rRNA transcription and rRNA production. Here, we summarize the current understanding of the mechanisms of noncoding RNA-mediated rRNA generation and regulation and their biological roles.